Job Insecurity as a Predictor of Job Satisfaction – Mediating Effect of Organizational Justice - Đorđević, Nemanja T. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
This paper discusses the effects of ubiquitous job insecurity on job satisfaction. This relationship is seen through the role of organizational justice. Therefore, the mediating effect that organizational justice has on the relationship between job insecurity and job satisfaction was examined. The sample consisted of 306 employed persons with an average length of service of 17 years and 6 months. A statistical method of parallel mediation was used. The results showed that all four cases of organizational justice measurement have a mediating effect. The greatest effect is in the case of interpersonal and informational justice. These two factors of organizational justice relate to interpersonal relationships and communication between management and employees, as well as employees with each other, i.e. availability, timeliness, completeness, and transparency in the placement of information within the organization. One of the explanations for this finding is the need of people who find themselves in uncertain situations to communicate and seek information about their position. Distributive and procedural justice are also statistically significant mediators. The results of the research show that organizational justice is an important factor in reducing the negative effects of job security on job satisfaction.